A call to action to address rural mental health disparities - Morales, Dawn A.; Barksdale, Crystal L.; Beckel-Mitchener, Andrea C. (Journal of clinical and translational science, 2020)
Rural residents in the USA experience significant disparities in mental health outcomes even though the prevalence of mental illness in rural and metropolitan areas is similar. This is a persistent problem that requires innovative approaches to resolve. Adopting and appropriately modifying the National Institute on Minority Health and Health Disparities research framework are the potential approaches to understanding how these disparities might be addressed through research. Using this research framework can facilitate interrogation of multiple levels of influence, encompassing complex domains of influence and consideration of the entire life course trajectory, which is consistent with several National Institute of Mental Health priorities.